Neopalimaia kupina . Neopalimaia kupina . Burning Bush . Неопалимая купина - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
This program was broadcast by Ostankino television (Moscow) in the Russian Federation and recorded by the moniotring group at the Research Institute of Radio Free Europe/Radio Liberty in Munich as part of their effort to track and analyze the official media of the countires of the former Soviet Union. Передача Российской государственной телевизионной и радиовещательной компании (РГТРК) "Останкино" (Москва, Российская Федерация) была записана группой мониторинга Исследовательского Института радиостанции Свободная Европа/Свобода (Мюнхен) как часть проекта по анализу официальных средств информации стран бывшего Советского Союза. Women's journal "Slavic Woman" celebrates its anniversary; discussion of women's position in Russia; interview with Olga Sorel, member of the staff of French Embassy in Moscow. Женский журнал "Славянка" празднует свой день рождения; обсуждение положения женщин в России; интервью с Ольгой Сорель, сотрудницей французского посольства в Москве.